Association of HLA-DRB1*15:02 and DRB5*01:02 allele with the susceptibility to systemic sclerosis in Thai patients - Louthrenoo W. (2014)
A genetic study, particularly in HLA-DRs, has never been performed in Thai patients with systemic sclerosis (SSc). This study was performed to investigate the association between the HLA-DR series in Thai SSc patients. HLA-DR subtypes were determined in 50 Thai SSc patients and 99 healthy controls (HCs). All SSc patients met the ACR classification criteria for SSc. HLA-DR typing was performed using INNO-LiPA HLA-DRB Decoder kits (INNOGENETICS) and reconfirmed using MICRO SSP HLA DNA Typing kits (ONE LAMBDA). The allele frequency (AF) of HLA-DR*15, compared with HC, was significantly higher in all SSc patients (41.0 vs 21.7 %, Pc = 0.0083) and SSc patients with anti-Scl70 antibody positive (anti-Scl70+) (47.1 %, Pc = 0.0018). Among the HLA-DR*15 alleles, the AF of the DRB1*15:02 was increased significantly in all SSc patients (29.0 vs 12.6 %, Pc = 0.0219) and SSc patients with anti-Scl70+ (32.4 vs 12.6 %, Pc = 0.0196). The AF of the HLA-DRB5*01:02 allele was also increased in all SSc patients (27.0 vs 12.6 %, Pc = 0.0166) and in SSc patients with anti-Scl70+ (29.4 %, Pc = 0.0124). The AF of the DR*04 was significantly lower in the SSc patients (1.0 vs 9.6 %, Pc = 0.0399). However, the AF of the DRB1*15:02 and DRB5*01:02 was not different among SSc patients with or without clinical manifestations (pulmonary fibrosis, digital pitting scar, sclerodactyly, myositis, and sicca symptoms). In addition, there was no significant association between clinical manifestations among individuals who carried HLA-DRB1*15:02 or DRB5*01:02. HLA-DRB1*15:02 and DRB5*01:02 alleles were significantly elevated in Thai SSc patients, especially in those with anti-Scl70+. The HLA-DRB1*04 was a protective allele against Thai SSc patients. © 2013 Springer-Verlag Berlin Heidelberg.